OPERATION COPYCAT - Manning, Matthew K. (North Mankato, Minnesota : Stone Arch Books, an imprint of Capstone Press, 2018)
When Sai Patel, fifteen, is framed for crimes he did not commit, his online friends of Drone Academy help him locate the Copycat drone and prove his innocence.
Keywords: Children's stories, English; English fiction